ANALYSIS AND RESULTS OF MORPHOLOGICAL CHANGES IN THE LUNGS OF SMOKERS - Ashirmatov Sherali Nurmakhamatovich. (Western European Studies, 2025)
Smoking, a widespread habit with a serious impact on health, remains a significant public health concern. Despite growing awareness of the risks associated with smoking, many individuals continue to succumb to this addiction. Understanding the facts about smokers and smoking habits can shed light on the challenges faced in addressing this global issue. In 2022, in collaboration with several research institutes of the Ministry of Agriculture, a study was conducted on the problem of nasvay and cigarettes. It is estimated that there are 4.5 million smokers in Uzbekistan. More than half of them, namely 2.4 million people, smoke cigarettes. The rest (2.1 million people) use nasvay. Smoking is a habit that has numerous harmful effects on human health. Smoking can lead to a multitude of short-term and long-term health problems, especially with regular use. Smoking harms the respiratory system, causes chronic obstructive pulmonary disease (COPD), and increases the risk of respiratory infections
Keywords: smoking; nicotine effects; alveoli